MOTIVASI, DISIPLIN DAN HASIL BELAJAR PESERTA DIDIK YANG MENGIKUTI EKSTRAKURIKULER OLAHRAGA DI SMK NEGERI 5 PONTIANAK - Monalisa Lestari; Mimi Haetami; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract The general problem of this research was "How were the motivation, discipline and learning outcomes of students who take sports extracurricular activities at vocational high school 5 Pontianak?. This study aimed to reveal: motivation, discipline and learning outcomes of students who take sports extracurricular activities at vocational high school 5 Pontianak.The research method used quantitative types with descriptive methods in the form of surveys. The population of class X students was 343 with a sample of 186 students. Data collection tools were questionnaires, observation and documentation.The results of this study can be concluded: 1) Learning motivation of students who take extracurricular sports at Pontianak State Vocational High School was  categorized enough with a percentage of 61.83%, 2) learning discipline students who take sports extracurricular at Pontianak State Vocational High School were  categorized less by percentage 58 , 89%, 3) the learning outcomes of students participating in sports extracurricular at Pontianak State Vocational High School were the highest score of 90 and the lowest score of 65 with the average students' learning score of 74.27 including a good category with completeness of 39.24%. Keywords: Discipline, Learning Outcomes, Motivation.